The Effect of a Guided Brainstorming Learning Model Using the Nusantara Flipchart on the Collaborative Attitudes of Fifth-Grade Students - Ni Putu Lingga Ayu Nadi; I Gusti Agung Ayu Wulandari; I Kadek Suartama (Indonesian Journal of Instruction, 2026)
In this era of globalization, collaborative behavior is a fundamental skill in facing global challenges. Currently, the low level of collaborative behavior in elementary schools is considered suboptimal. This study aims to analyze the effect of the brainstorming learning model using the Nusantara sticky board media on the collaborative behavior of fifth-grade elementary school students. This study is a quasi-experimental design using a non-equivalent post-test only control design. The population of this study was all fifth-grade elementary school students totaling 524 students consisting of 16 classes. The sample of this study used a cluster random sampling technique. Data analysis of this study used descriptive statistics and inferential statistics. Collaborative attitude data collection used a non-test method in the form of an observation sheet. Based on the results of the collaborative attitude data analysis, it was obtained that t count > t table so that H0 was rejected and Ha was accepted. This indicates that there is a significant influence of collaborative attitudes between the group of students who were taught with the brainstorming learning model assisted by the Nusantara sticky board media and the group of students who were taught with conventional learning.